Postoperative Limb-Offset Discrepancy Notably Affects Soft-Tissue Tension in Total Hip Arthroplasty. (21st September 2016) - Takao, Masaki; Nishii, Takashi; Sakai, Takashi; Sugano, Nobuhiko
Abstract : Background: Inadequate soft-tissue tension in total hip arthroplasty is regarded as one cause of dislocation or abductor muscle weakness. The purpose of the present study was to assess how the postoperative discrepancy in limb offset (consisting of both femoral offset and acetabular offset) affects soft-tissue tension compared with other factors among patients with unilateral hip disease undergoing total hip arthroplasty. Methods: A total of 89 consecutive patients underwent mini-incision total hip arthroplasty involving an anterolateral or posterior approach and with use of a computer navigation system. Soft-tissue tension was measured by applying traction amounting to 40% of body weight with the joint positioned at 0°, 15°, 30°, and 45° of flexion. The separation between the cup and the prosthetic head was measured using the navigation system. Results: The cup-head separation differed significantly for varying angles of flexion (p < 0.001), with the greatest distance noted at 15° of flexion (mean and standard deviation, 11 ± 5 mm). Stepwise multiple regression analysis showed that postoperative limb-offset discrepancy, an anterolateral approach, and preoperative abduction range of motion were correlated with the cup-head separation at 15° of flexion. Postoperative limb-offset discrepancy was negatively correlated with the cup-head separation at 0°, 15°, and 30° of flexion. Conclusions: Postoperative limb-offset discrepancy significantly affected the soft-tissue tension in total hip arthroplasty at varying degrees of flexion. This indicated that it is important to restore normal limb offset without overlengthening to obtain adequate soft-tissue tension in total hip arthroplasty. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.